1997
DOI: 10.1063/1.120339
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of amorphous hard carbon films produced by cathodic arc deposition

Abstract: The thermal stability of amorphous hard carbon films produced by cathodic arc deposition was studied by Near Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy, Raman spectroscopy. and nanoindentation evaluation. Pure carbon films of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 26 publications
6
37
0
Order By: Relevance
“…S1). Since TEY detected NEXAFS is a surface sensitive technique with electron escape depth~5 nm [43], this result indicates no change to surface composition. The increased intensity at 300 eV is likely due to the subtle structural rearrangement of SeP3MEET with more side-chains at the film/air interface after annealing.…”
Section: Molecular Doping Of the Polar Layermentioning
confidence: 88%
“…S1). Since TEY detected NEXAFS is a surface sensitive technique with electron escape depth~5 nm [43], this result indicates no change to surface composition. The increased intensity at 300 eV is likely due to the subtle structural rearrangement of SeP3MEET with more side-chains at the film/air interface after annealing.…”
Section: Molecular Doping Of the Polar Layermentioning
confidence: 88%
“…The C 1s → ‫ء‬ peak in the graphite spectrum is located at 285.5 eV, which is the proper location for ordered sp 2 bonding, and the C 1s → ‫ء‬ transition begins at a higher energy ͑Ͼ290 eV͒ which is a known characteristic of ordered sp 2 -bonded carbon. The NEXAFS TEY spectrum of as-deposited ta-C exhibits a peak at 285.0 eV due to the C 1s → ‫ء‬ transition for disordered carboncarbon sp 2 -hybridized bonds, 21 and a broad hump starting above 288 eV and extending up to 305 eV due to the C 1s → ‫ء‬ transition for disordered carbon-carbon bonds. These are all typical features of amorphous carbon films.…”
Section: Resultsmentioning
confidence: 99%
“…Alam et al 12 used nuclear magnetic resonance ͑NMR͒ spectroscopy to reveal than the sp 3 content of an initially 82% sp 3 -bonded ta-C film ͑grown using the same method and growth system in this work͒ changed by Ͻ2% when heated to 650°C for annealing times up to 4 min. Raman and near-edge x-ray absorption fine structure ͑NEXAFS͒ spectroscopies were employed by Anders et al 21 on ta-C films deposited by cathodic arc and annealed up to 850°C for 15 min, and they found that while Raman showed only subtle spectral changes, NEXAFS revealed significant increases in the sp 2 character for films annealed above 700°C. Orwa et al used transmission electron microscopy ͑TEM͒ combined with EELS and Raman spectroscopy to determine if the sp 2 bonds ta-C ͑filtered cathodic arc grown͒ tend to cluster at higher annealing temperatures ͑up to 1100°C͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally DLC has been prepared by Pulsed Laser Deposition (PLD) [4], Filtered Cathodic Arc (FCA) [5,6] and Mass Selected Ion Beam (MSIB) [7]. DLC is currently used as overcoats in magnetic disks and heads, as an ultra thin layer (less than 10 nm), for protection of the magnetic media against wear and environmental degradation.…”
Section: Introductionmentioning
confidence: 99%